THE DECREASING EFFORTS ON 45 BUILDING IN PARAHYANGAN CATHOLIC UNIVERSITY BANDUNG ACCORDING TO GREENSHIP NB1.2 CRITERIA - Alexander Gunawan ; Yasmin Suriansyah (Riset Arsitektur (RISA), 2018)
Abstract- Every projects should be sustainable and enviromentally friendly. There are many organization that promote a sustainable construction projects, one of them is Green Building Council Indonesia (GBCI), with its GREENSHIP rating tools.Building45 is one of the latest buildings in UNPAR university complex. After doing pre-research based on Building 45 condition, the building doesn’t meet a few green building criteria based on GREENSHIP New Building 1.2. One of it is the OTTV value, Building 45 has a high OTTV value. A research to optimize the OTTV value should be conducted.The research was conducted with simulation method to optimize the OTTV value but didn’t interfere the other green building  aspect such as its natural lighting. The variable of the optimization is WWR value, shading element, and the transparent material of the building.The most effective variable to reduce OTTV value is by WWR arrrangement.The OTTV value can be optimized to reach 28.62 W/m2, and 39.2% of the first floor and 30.3% of the second floor area still have natural lighting iluminousity of more than 300 lux. The OTTV optimization can increase the green building rating of Building 45 by 5 points based on GREENSHIP NB 1.2. Key Words: Optimalization, OTTV, GREENSHIP NB 1.2, WWR, natural lighting